Taste detection of the non-volatile isothiocyanate moringin results in deterrence to glucosinolate-adapted insect larvae. (October 2015) - Müller, Caroline; van Loon, Joop; Ruschioni, Sara; De Nicola, Gina Rosalinda; Olsen, Carl Erik; Iori, Renato; Agerbirk, Niels
Abstract : Graphical abstract: The non-volatile isothiocyanate moringin deterred larvae of the sawfly Athalia rosae and two Pieris species, and elicited response from a deterrent taste neuron in P. brassicae . Recovery of moringin applied to leaf discs for feeding assays was high. Highlights: Glucomoringin and moringin were characterized by NMR and tandem MS/MS. The glycosylated isothiocyanate moringin deterred glucosinolate-adapted insect larvae. Moringin elicited activity in a deterrent-sensitive taste neuron in Pieris brassicae . Isothiocyanates and glucosinolates were quantitated in bioassays and recoveries were high. Abstract: Isothiocyanates (ITCs), released from Brassicales plants after hydrolysis of glucosinolates, are known for their negative effects on herbivores but mechanisms have been elusive. The ITCs are initially present in dissolved form at the site of herbivore feeding, but volatile ITCs may subsequently enter the gas phase and all ITCs may react with matrix components. Deterrence to herbivores resulting from topically applied volatile ITCs in artificial feeding assays may hence lead to ambiguous conclusions. In the present study, the non-volatile ITC moringin (4-(α-l -rhamnopyranosyloxy)benzyl ITC) and its glucosinolate precursor glucomoringin were examined for effects on behaviour and taste physiology of specialist insect herbivores of Brassicales. In feeding bioassays, glucomoringin was not deterrent to larvae of Pieris napi (Lepidoptera: Pieridae) and Athalia rosae (Hymenoptera: Tenthredinidae), which are adapted to glucosinolates. Glucomoringin stimulated feeding of larvae of the related Pieris brassicae (Lepidoptera: Pieridae) and also elicited electrophysiological activity from a glucosinolate-sensitive gustatory neuron in the lateral maxillary taste sensilla. In contrast, the ITC moringin was deterrent to P. napi and P. brassicae at high levels and to A. rosae at both high and low levels when topically applied to cabbage leaf discs (either 12, 120 or 1200 nmol moringin per leaf disc of 1 cm diameter). Survival of A. rosae was also significantly reduced when larvae were kept on leaves treated with moringin for several days. Furthermore, moringin elicited electrophysiological activity in a deterrent-sensitive neuron in the medial maxillary taste sensillum of P. brassicae, providing a sensory mechanism for the deterrence and the first known ITC taste response of an insect. In simulated feeding assays, recovery of moringin was high, in accordance with its non-volatile nature. Our results demonstrate taste-mediated deterrence of a non-volatile, natural ITC to glucosinolate-adapted insects.